Pengembangan Media Pembelajaran Interaktif PowerPoint berbasis Inkuiri Terbimbing pada Materi Hukum Dasar Kimia dan Stoikiometri Kelas X SMA/MA - Riri Andika Sari; Syamsi Aini (Universitas Negeri Padang, 2022)
Basic law material of chemistry and stoichiometry have been learned in 2013 curriculum was studied in class X SMA or MA on even semester. Based on 2013 curriculum guidance, the material should be taught by scientific approach and practicum method. However, due to limited in class duration and students lack of preparation in term of discussion needs, those approach and method became difficult to implement. Thus, this learning process can be helped with a learning media. One of learning media that can be implemented is an interactive PowerPoint learning media with guided inquiry based. This research aimed to produce valid and practical interactive PowerPoint learning media with guided inquiry based for basic laws of chemistry and stoichiometry subject of X grade in SMA or MA. The method that used in this research was R and D method with 4D development model which was restricted to development phase. The techniques for data analysis was Aikens V that showed score as followed 0.82 for content validation, 0.84 for construct validation, and 0.96 for media expert validation which were all classified as valid result. The results of practicality test for learning media by teachers and students are 93 percent and 85.8 percent with very practical category.